Analisis Pengelolaan Zakat Profesi dalam Program Pengentasan Kemiskinan oleh BAZNAS Kabupaten Situbondo - Arif, Zeiniye; Muhammad; suharto, Babun (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the management of professional zakat in poverty alleviation programs implemented by the National Amil Zakat Agency (BAZNAS) of Situbondo Regency. Poverty remains a persistent socio-economic problem that requires alternative instruments beyond government fiscal policies, including Islamic social finance mechanisms such as zakat. This research employs a qualitative approach using document-based analysis. Data were obtained from official reports of BAZNAS Situbondo, relevant regulations on zakat management, and statistical data on poverty issued by authorized institutions. The data were analyzed descriptively and analytically to examine the stages of zakat management, including collection, distribution, and utilization of professional zakat funds in relation to poverty alleviation objectives. The findings indicate that the management of professional zakat by BAZNAS Situbondo has been structured in accordance with existing regulations and oriented toward both consumptive and productive poverty alleviation programs. However, several challenges remain, particularly in optimizing the potential of professional zakat and strengthening its integration with broader poverty reduction strategies. This study contributes to the literature on Islamic economics by providing empirical insights into local-level zakat management and offers policy recommendations for improving the effectiveness of professional zakat as an instrument for poverty alleviation. Keywords : Professional Zakat; BAZNAS; Poverty Alleviation; Islamic Economics